Effect of Seeding Strategy on the Efficiency of Brand Spreading in Complex Social Networks - ShiYong, Zheng; JiaYing, Li; Wei, Wang; HaiJian, Wang; Akram, Umair; Lei, Wang; BiQing, Li (Frontiers in Psychology, 2022)
In social networks, consumers gather to form brand-communities, and the community structure significantly impacts the dissemination of brand information. Which communication strategy is more conducive to information dissemination in different structured brand communities. Considering the above factors, we propose the word-of-mouth (WOM) agent model based on the traditional rumor model and bass model, in which the brand WOM spreading is affected by the user’s psychological mechanisms, the network structure and other factors. Through simulation experiments, the results showed the following: (1) The conclusion of the traditional bass model is no longer applicable to social marketing in brand information diffusion, that is, the effect of external marketing stimulation on information dissemination is limited. (2) The communication effect and efficiency of information in different structures of the learning-community network are very different. (3) The strategy of hub nodes is not suitable for all types of networks, and the impact of different seeding strategies on the efficiency and effect of brand information dissemination was verified. Finally, the conclusion was verified again using the social network data on Facebook.